Απόφαση συνεδρίασης του Δημοτικού Συμβουλίου Κοζάνης σχετικά με την οικονομική ενίσχυση απόρων Δημοτών
Απόφαση συνεδρίασης του Δημοτικού Συμβουλίου Κοζάνης σχετικά με την οικονομική ενίσχυση απόρων Δημοτών